Pengaruh Fomo dan Affiliate Marketer Terhadap Minat Beli Konsumen di Nekko Fashion Store - Ni Luh made Risnia Dewi; Komang Widhya Sedana Putra (As-Syirkah: Islamic Economic & Financial Journal, 2025)
This research examines the influence of Fear of Missing Out (FOMO) and Affiliate Marketing on consumer purchase intention at Nekko Fashion Store. In this rapidly developing digital era, marketing strategies have shifted significantly, with FOMO and affiliate marketing emerging as prominent trends. Consumers, especially the younger generation, often feel compelled to purchase products due to the fear of missing out on viral trends, while affiliate marketing systems utilizing influencers further enhance consumer purchase intention. This study focuses on Nekko Fashion Store consumers in Denpasar Selatan, Bali, who actively shop online and are influenced by digital marketing strategies. Previous research has highlighted the impact of digital marketing and influencers on purchasing decisions, but has not specifically addressed the combined role of FOMO and affiliate marketing in shaping purchase intention within the fashion industry. Therefore, this study aims to analyze the influence of FOMO, affiliate marketing, and their interaction on consumer purchase intention at Nekko Fashion Store.